SELF-CARE ISSUES OF COUNSELORS UNDERGRADUATE TRAINEES IN COUNSELING INTERNSHIPS AT SCHOOL: A CASE STUDY - Siti Izati Ismail; Nurul 'Ain Mohd Daud, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Counselor trainees’ self-care has been receiving rising attention due to burnout and lack of personal growth among trainees. Although some colleges with counselor training programs have required physical check-ups for trainees, little research has been done to examine trainee self-care issues. Employing a phenomenological research design, the main research question for the case study was to examine self-care issues concerning counselor trainees in counseling internships. Interview questionnaires, observation, journal, portfolio collection, and audiovisual recordings were used as data collection instruments. Additionally, the researcher’s self-examinations, reactions, feelings, and ethical discussions were noted. The themes extracted from data are mixed feelings toward doing one’s own counseling, taking advice (for those already doing self-care behaviors), effects on their children, and positive effects when participants make time for their self-care. The qualitative results are then discussed and compared to previous related research. The paper concludes with implications and specific recommendations for counselor training and future research. The model of self-care from Lazarus and Folkman (1984) provides the theoretical underpinning for understanding of the findings, as the researchers took into consideration that the perception of coping is a stressor in the model. In conclusion, the authors’ findings suggest that counselor trainees have self-care issues that warrant further research attention in the form of both quantitative and qualitative confirmatory studies.